The development of the system for identification of seismic stability and monitoring of origin of anomalous seismic processes - Алиев, Тельман Аббас; Аббасов, Али Мамед; Гулуев, Гамбар Агаверди; Пашаев, Фахрад Гейдар; Саттарова, Улькар Эльдар (Eastern-European Journal of Enterprise Technologies, 2015)
To minimize damage from earthquakes, intelligent robust noise technology and a system that allows to combine the monitoring of the latent period of violation of seismic stability with the monitoring of origin of anomalous seismic processes (ASP) is proposed. The system includes a network of seismic-acoustic stations for monitoring the beginning of ASP, located in different areas of the region and the local units for noise monitoring of seismic stability, which are installed in the most vulnerable structures of all controlled construction objects. In order to identify the latent period of the ASP origin and violations of seismic stability of construction objects (SSCO), noise is used as a carrier of diagnostic information. Since June 2010, operation of the network of seismic-acoustic stations and stations for monitoring the violations of SSCO showed that they can be used as a tool to identify the focus areas of expected earthquakes, and to control microchanges in SSCO.